Assessing the impact of phylogenetic incongruence on taxonomy, floral evolution, biogeographical history, and phylogenetic diversity. Issue 4 (1st April 2015) - Zhang, Qiang; Feild, Taylor S.; Antonelli, Alexandre
Abstract : Premise of the study: Phylogenetic incongruence between "gene trees" and "species trees" has been widely acknowledged in phylogenetic research. Conflicts may emerge from several processes including paralogy, hybridization, and incomplete lineage sorting. Although phylogenetic incongruence appears common, its impact on many phylogeny‐based analyses remains poorly understood. Methods: We examined the occurrence of phylogenetic conflict between nuclear (ribosome ITS) and plastid ( rbcL, trnL ‐ F, rpl20 ‐ rps12, and rps16 intron) loci in the ancient angiosperm family Chloranthaceae. Then we investigated how phylogenetic conflict bears on taxonomic classification within the family as well as on inferences on biogeographical history, floral evolution, and measures of phylogenetic diversity (PD). Key results: We found evidence for significant phylogenetic incongruence between plastid and nuclear data in the genus Hedyosmum . Within Hedyosmum, our results did not support previous subgeneric classification of the genus. Division of sections within subgenus Tafalla was supported by the ITS data but not by the plastid data set. As a consequence, we showed that inferring the evolution of key floral characters and geographical history within Hedyosmum depends on the phylogenetic data used. Both data sets yielded similar PD measures across genera, but we found contrasting PD measures in Hedyosmum, even after correcting for rate heterogeneity. Conclusions: Our study demonstrated that phylogenetic conflict not only affects the inference of organismal relationships but also impacts our understanding of biogeographical history, morphological evolution, and phylogenetic diversity.